Translation Prospects in Malayalam and Tamil - Biju P.V (Language in India, 2016)
Translation is a method of literature attempting to reflect and illuminate a culture from outside. Many translated works from world literature has attracted wide publicity in Malayalam due to their translation clarity and language. Tamil and Malayalam are the two prominent languages among the Dravidian Language family, which are engaged in close and intense cultural and literal interactions. Since both of them belong to the same language family, they are closely connected in cultural and lingual aspects. “Tamil and Malayalam became two distinct languages around 10 th century AD and are closely connected in the Dravidian Language family. There are several similarities between these two languages. People who speak these languages also have many similarities” (Nachimuthu, 2005:97). Such similarities are also visible in works translated from Tamil to Malayalam and vise-versa. Among the authors translated from Malayalam to Tamil, prominent ones are Thakazhi Sivasankarappillai, Vaikkom Muhammed Basheer, Karur neelakandappillai, M. Govindan, O.V. Vijayan, Attoor Ravivarma, M.T. Vasudevan Nair, Zakariya, Balachandran Chullikkadu, and K. Sachidanandan. Novel translations were mostly based on realistic nature. Its magnitude has been transformed in later translation works. The aim of this paper is to examine which types of works are widely accepted in contemporary Malayalam and Tamil literatures.